فاعلية أنموذج التسريع المعرفي (CASE) في قدرة طلاب الصف الثاني المتوسط على حل المسائل وتنمية استطلاعهم الفيزيائي - ياسين عبدالله عبدالرزاق; سالم قاسم العزاوي أحمد (Journal of College of Education, 2020)
The objective of the research was to identify the effectiveness of the cognitive acceleration model in the ability of the second grade students to solve the mathematical problems of physics and the development of their physical survey. The sample consisted of (78) second grade students who were chosen intentionally from the middle of the martyr Ali al-Ramli for boys in Mosul For the academic year (2018-2019) and then divided them into two equal groups in the first issue of experimental study on the model of the acceleration of knowledge (CASE) And the second was an officer studied according to the usual method. The two researchers rewarded the sample members in a number of variables, namely, intelligence, physical survey, science degree for the first intermediate grade. To achieve the objective of the research and test hypotheses, the researchers relied on the first two tools to test the physical issues, The physical survey prepared by al-Tai (2016) The instruments were characterized by honesty, consistency and cykometric characteristics. The researchers then assigned the teacher of the material in the school to carry out the research experiment in the second course. After the completion, the researchers applied the two tools periodically and analyzed the data statistically using the TI test for two independent samples :- 1 - There is a significant statistical difference at (0.05) between the average ability of students in the experimental and control groups to solve the physical problems and for the benefit of the pilot.2 - There is a difference of statistical significance at (0.05) between the average development of the physical survey in the members of the experimental and control groups and for the benefit of the pilot.At the end of the experiment, the researchers came up with a number of conclusions and recommendations as well as proposals for future research